Forms of temporality and historical time in the work of Johann Gottfried Herder - Schmidt, Johannes 1975-; Steinby, Liisa 1952- (Routledge, 2024)
This edited collection is the first volume solely dedicated to research on Johann Gottfried Herders understanding of history, time, and temporalities
Keywords: Herder, Johann Gottfried von -- 1744-1803; Zeitlichkeit; Geschichtlichkeit; European history; Europäische Geschichte; Geschichtsschreibung, Historiographie; HISTORY / Europe / General; HISTORY / Historiography; HISTORY / Social History; Historiography; Modern history to 20th century: c 1700 to c 1900; Social & cultural history; Sozial- und Kulturgeschichte; Aufsatzsammlung